2006
DOI: 10.1021/ic051287+
|View full text |Cite
|
Sign up to set email alerts
|

A Bidentate Terephthalamide Ligand, TAMmeg, as an Entry into Terephthalamide-Containing Therapeutic Iron Chelating Agents

Abstract: A new bidentate 2,3-dihydroxyterephthalamide ligand, 2,3-dihydroxy-N,N′-bis(2-methoxyethyl)terephthalamide (TAMmeg), has been prepared. The ligand, its synthetic precursor 2,3-bis(benzyloxy)-N, N′-bis(2-methoxy-ethyl)-terephthalamide (BnTAMmeg), and its iron complex have been structurally characterized by X-ray diffraction. BnTAMmeg crystallizes in the monoclinic space group P2 1 /n with cell parameters a = 14.4976 (14)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…6 Moreover, ligand properties such as charge and solubility can be more easily modified using TAM units relative to other chelating units described in the literature. 6 c Additionally, unlike previously reported 89 Zr chelators, we incorporated into our ligand scaffolds a pendant arm containing a primary amine, which can be easily functionalized for conjugation to a variety of targeting ligands. These ligands were prepared by condensation of tetraamine and activated di-acid intermediates under high dilution (H.D.)…”
mentioning
confidence: 99%
“…6 Moreover, ligand properties such as charge and solubility can be more easily modified using TAM units relative to other chelating units described in the literature. 6 c Additionally, unlike previously reported 89 Zr chelators, we incorporated into our ligand scaffolds a pendant arm containing a primary amine, which can be easily functionalized for conjugation to a variety of targeting ligands. These ligands were prepared by condensation of tetraamine and activated di-acid intermediates under high dilution (H.D.)…”
mentioning
confidence: 99%
“…Herein, upon addition of increased concentration of Fe (III), an increased absorbance at λ 300 nm was observed, and concomitantly, the absorbance peak at λ 450 nm was compromised. It is well established that catecholate units in naturally occurring siderophores are efficient and necessary binding sites for ferric ion; , however, literature also reveals that synthetic siderophores possessing a phenol substituent adjacent to a sp 2 hybridized nitrogen atom exhibits good iron chelation affinity. Thus, our prepared IL-2 and IL-3 comprising similar binding sites (Figure ) also shows good affinity toward ferric ion selectively as compared with other cations as evidenced by UV–visible absorption spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 1 contains binding units similar to siderophores, which are the iron chelating compounds secreted by microorganisms to facilitate the active transport of iron [11]. It has been demonstrated that many siderophores and iron chelating agents comprise a phenol substituent adjacent to a sp 2 hybridised nitrogen atom as depicted in structure 2 (Scheme 1) [12][13][14].…”
Section: Resultsmentioning
confidence: 99%